Michael Townsend's Amazing Greek myths of wonder and blunders. - Townsend, Michael (Michael Jay), 1981- (Dial Books For Young Readers, 2010)
A collection of comics that interpret Greek myths, depicting stories about characters such as King Midas, Pandora, Arachne, Icarus, Hercules, and others.